Characterisation of polymorphisms on the promoter region of the human histamine 4 receptor - Micallef, Stephany (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2013)
The human histamine 4 receptor (HRH4) is the recently discovered receptor in the histamine GPCR family. It is mainly expressed in haematopoietic cells but recent publications provide evidence that it is both expressed and functional on neurons in mammalian CNS. This study targets genetic polymorphism in the promoter region of HRH4, for which in preliminary unpublished data it is indicated that a length polymorphism, a variable number of tandem repeats (VNTR), i.e., CAA repeats, is more common in schizophrenia patients. The aim of the project is to test for association for polymorphisms on HRH4 gene using genome-wide association studies (GWAS) from the International Schizophrenia Consortium, genotype HapMap samples and establish linkage disequilibrium (LD) with known SNPs, clone the putative promoter region of HRH4 in a reporter plasmid, and finally analyse these clones in a cell-based assay for functional impact on gene expression. Linkage analyses showed that while there is no strong significance with schizophrenia, the 13 CAA microsatellite repeat has a high LD with rs17797945 (r2 = 0.956) which is a SNP flagged by the GWAS analysis that had a weak association to schizophrenia (P = 0.007879). Genotyping HapMap samples also indicated that this VNTR region varies between 10 (10R) and 13 (13R) to 19 triplet repeats (19R) with a SNP at the end of the triplet repeat. These genotypes were cloned into a standard vector, sub-cloned into a reporter vector (pGL3-basic) and mutated to obtain the respective allele variants. The sequence cloned for all VNTR polymorphisms was from -2044 bp to -1 of the promoter region as described by Coge et al. The 10R was used for further analysis to identify the functional promoter where it was extended at the 5’-end and the 3’-end including exon 1. The -2044 bp 13R reporter construct was also extended on the 3’-end and analysed since this had the highest allele frequency (27%). The promoter constructs were assayed on a Dual-Glo luciferase assay, where the promoter length constructs were transiently transfected into a mammalian cell line (HEK293T) and normalised with the renilla vector pRL-SV40. Gene expression of firefly luciferase was directly quantified as transcriptional activity of the promoter region. The promoter sequence described in silico by Coge et al ranging from -2044 bp to -1 did not reach statistical significance when compared to the promoter less vector (pGL3-Basic), however the promoter sequence tested in vitro ranging from -705 bp to +194 bp was identified as the functional promoter with P < 0.001 when compared to pGL3-basic vector. This is the first study that analyses the promoter region of the HRH4 biologically in a cell-based assay.
Keywords: Pharmacy & Pharmaceutical Sciences, Ph.D.; Ph.D. Trinity College Dublin